An overview of blockchain technology in the South African financial industry - Maboe, Realeboga (My University, 2018)
Blockchain, the new kid on the block, has the potential ability to change the way data are handled in the financial industry giving it a disruptive nature worthy of being explored and understood. However, not much is known and understood about these applications in the world, let alone in the South African landscape. The introduction of new financial innovations with the promise of being disruptive in nature always bring a sense of uncertainty and concern about the impact this new technology will have on the current way of doing things. Due to its highly technical nature, Blockchain is yet to be fully understood by many who stand to benefit from adopting it. Apart from understanding how it works, its application is paramount to possibly bringing innovative changes to the financial sector. The mandate is to attempt to fully unpack the nature of the phenomenon with relation to financial innovation and to see the process by which it evolves or is experienced. The purpose of this study is to provide an exploratory literature review of the full nature of Blockchain technology and bitcoin and investigate how the innovation evolved and is being experienced in South Africa. This will be done through looking at secondary sources with focus on the application it has as a new financial innovation within the financial industry in South Africa. This is still in the process of being done and begs the question of whether bitcoin is an important disruptive financial innovation which is here to stay in South Africa or not. The exploration aims to prepare a theoretical and practical basis for future studies.
Thesis submitted in fulfilment of the requirements for the degree of Master of Management in Finance and Investment, Faculty of Commerce, Law and Management, Wits Business School University of the Witwatersrand, October 2018
Keywords: Blockchains (Databases); Banks and banking--South Africa